(untitled) (The Pretoria Student Law Review, 2021)
This article examines the conflict between procedure and substance. Substance should be favoured above procedure because where substance is at the heart of a legitimacy mechanism, collective decision-making can take place that makes a positive contribution and constructs an ethical society. Lawfulness and morality should be connected to give practical effect to such a model. Apartheid laws were collective decisions that were procedurally lawful, but were morally unsatisfactory. When a citizen faces a law that is immoral, and in terms of Aquinas irrational, it is not a law at all, and it should be resisted.